TRADISI HARMONY IN NATURE DALAM AL-QUR’AN - Nur Afiyah Febriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2012)
The controversy about the causes of the environment damage isspread out nowadays. The root of this problem is the people’s ideologyabout nature which is very stiff. Anthropocentrism people legitimate theiraction in natural exploitation. Meanwhile, if it is analyzed comprehensively,there are 800 verses of kawniyah verses in al-Qur’an that are relatedto the universe. This article tries to explore the verses which explainthe ideal concept of interaction patterns and interconnection betweenman and the ecosystem. This paper shows that harmony-in nature visionof al-Qur’an possesses an eco-humanist theology.